Guía digital para la metodología experimental en el aprendizaje de Química con estudiantes de segundo BGU de la Unidad Educativa "Miguel Ángel León Pontón" - Guevara Silva, Josselyn Magaly (2023)
This study addresses the integration of digital guides in the teaching process of Chemistry for students in the second year of upper secondary in "Miguel Ángel León Pontón" high school. The problem is that students fear learning chemistry because they only learn theory, postulates, and formulas, but there is no experimentation. The general objective of the research is to propose a digital guide for the experimental methodology in the learning of Chemistry for students in the second year of upper secondary in "Miguel Ángel León Pontón" high school." A survey was administered to the students to achieve the objective. The main result of the research revealed a positive attitude and a generalized acceptance on the part of the students towards the integration of digital guides and technology in their learning process of Chemistry. As for the methodology implemented, it was non-experimental because the variables were not deliberately manipulated during the study. Information was collected from various bibliographic sources, such as books, scientific journals, and theses in the UNACH repository. Based on the results obtained, the research concludes that the proposal of a digital guide for experimental methodology in teaching chemistry is viable and relevant. Therefore, it is recommended the creation and subsequent implementation of this digital guide for a new educational experience for the students in the second year of upper secondary in "Miguel Ángel León Pontón" high school.